Microspectral laser analysis of selected dental implants - Sołkiewicz, Edyta; Arcimowicz, Bronisław; Sidorowicz, Krzysztof; Sokalski, Jerzy (Journal of Medical Science, 2014)
Aim. In the paper the microspectral analysis of selected dental implants was presented.Material and methods. The following implants were analysed: Osteoplant, Keystone Dental, Mozo Grau, Alpha Bio, Sky, and Implant Direct. The probes of each implant were analysed in the laser spectrophotometer.Results. The result of the study was: Keystone Dental, Mozo Grau, Alpha Bio and Implant Direct titanium implants were shown to include aluminium and vanadium components while the Osteoplant and Sky implants to be made of pure titanium.